Profiles of the Hard to Employ and the Implications for Job Success - Elizabeth B. Bolton (EDIS)
This report, Profiles of the Hard to Employ and the Implications for Job Success, is part of the UF/IFAS Welfare-to-Work Initiative (Grant #A6218) funded by the Florida Agency for Workforce Innovation (formerly Florida Department of Labor and Employment Security). The Principal Investigator is Elizabeth B. Bolton, Professor of Community Development, Department of Family, Youth and Community Sciences. First published November, 2002.